Pacific Datathon region 2024: 50 young Colombians transforming data into solutions - Urbano, Angélica; Rankin, Sara; Salas, Daniela (CGIAR System Organization, 2024)
In the context of the current challenges facing food, land and water systems in Colombia, the power of data has become a fundamental tool to generate innovative and sustainable solutions. The Pacific Datathon is framed within this urgent need to harness information to address critical issues related to biodiversity, climate change and food security. This event brought together young minds from the region to work in teams, using data to propose effective responses to challenges that put our natural resources and the health of our communities at risk.